A Personalized Approach to Parkinson’s Disease Patients Based on Founder Mutation Analysis - Giladi, Nir; Mirelman, Anat; Thaler, Avner; Orr-Urtreger, Avi (Frontiers in Neurology, 2016)
While the phenotype of Parkinson disease (PD) is heterogeneous, treatment approaches are mostly uniform. Personalized medicine aims to treat diseases with targeted therapies based on cumulative variables including genotype. We believe that sufficient evidence has accumulated to warrant the initiation of personalized medicine in PD based on subjects genotype and provide examples for our reasoning from observations of GBA and LRRK2 mutations carriers. While PD patients who carry the G2019S mutation in the LRRK2 gene seem to develop relatively mild disease with more frequent postural instability gait disturbance phenotype, carriers of mutations in the GBA gene tend to have an early onset, rapidly deteriorating disease, with more pronounced cognitive and autonomic impairments. These characteristics have significant implications for treatment and outcome and should be addressed from an early stage in the attempt to improve the patient's quality of life.